Bioactivity-guided isolation and structural characterization of endogenously accreted raphide crystals in Ipomoea aquatica Forssk. - Chakraborty, N; Das, A K; Manna, R K; Das, B K; Mandal, B (Journal of the Inland Fisheries Society of India, 2020)
Bio-minerals are one of the secondary plant metabolites that are imperative for their existence. Raphides or calcium oxalate (CaC2O4) crystals are the most abundantly synthesized bio-minerals in plants which help channelize the excess calcium absorbed. Raphides have been isolated (1.6% dry weight) and purified by chromatographic process from aqueous fraction of Ipomoea aquatica leaves. Direct bio autography followed by agar well diffusion assay reveals the in-vitro antimicrobial property of the crystals against fish pathogen Citrobacter freundii with MIC< 50 ppm. The atomic force microscopy predicts a hydrous inorganic salt displaying average peaks between 4-5 nm with homogeneity of dispersion. The crystal exhibited moderate level of free radical scavenging activity with IC50 at 0.144 mg/ml. The molecular structure characterization of the crystal by the magnetic resonance and infra-red spectra further confirmed the presence of raphides. Key words Ipomoea aquatica; Calcium oxalate; Atomic Force Microscopy; Structure characterization; Citrobacter freundii; Antioxidant.